Product Development of Germinated Black Glutinous Rice Drink in a Sachet as Affected by Roasting and Brewing Time - Jongrattanavit, Kankanit; Pothinuch, Pitchaya; Pichaiyongvongdee, Suwanna; Nukit, Natchanok; Bangsiri, Naraet (Journal of Food Health and Bioenvironmental Science, 2023)
Germinated black glutinous rice (GBGR) drink in a sachet was developed. The effects of roasting time (0, 5, 10 and 15 min) and brewing time (3, 5, 7, 10 and 15 min) on color, chemical compositions and antioxidant capacity were investigated. Prolonged roasting time increased L*, positive b*, C* and h° values, whereas decreased positive a* value, resulting in lighter color. Ash and carbohydrate contents were higher when longer roasting time was applied; however, aw, moisture and protein contents were lower. GABA contents (61.04 mg/kg) retained in GBGR with 5 min-roasting time. Fat, crude fibers, total phenolic (TPC), total anthocyanin (TAC) contents and DPPH scavenging capacity did not significant change according to roasting time. Regarding brewing time with water at 98°C, L* and h° values of GBGR drink decreased. Higher TPC, TAC and DPPH scavenging capacity of GBGR drink were induced by using short brewing time 3-5 min). Therefore, roasting and brewing time of 5 and 3 min, respectively, were recommended for healthy drink production from GBGR. GABA concentration of 0.17 mg/150 mL was detected in finished product. For consumer acceptability test, GBGR drink was liked moderately and 77% of consumers would like to buy the product. Physical, chemical and microbial changes of the product prototype during storage time of 98 days were accepted following the Thai agricultural standard TAS 4404-2012 Good manufacturing practices for germinated brown rice standard.